2013
DOI: 10.1016/j.ijscr.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent benign schwannoma of the scalp: Case report

Abstract: Schwannoma may present as multiple lesions in a multilobulated scalp lesion and should be considered as differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Though we did not have any facility, immunohistochemical approach is usually undertaken in current assessment of soft tissue tumour especially with unusual clinicopathological features as ours. Schwannomas are often associated with cystic changes compared to PN, however, on histology, the absence of a mixture of two growth patterns Antoni A, and Antoni B (Asuquo et al 2013), in Figure 4b and the characteristic features of PN confirmed the diagnosis.…”
Section: Discussionmentioning
confidence: 84%
“…Though we did not have any facility, immunohistochemical approach is usually undertaken in current assessment of soft tissue tumour especially with unusual clinicopathological features as ours. Schwannomas are often associated with cystic changes compared to PN, however, on histology, the absence of a mixture of two growth patterns Antoni A, and Antoni B (Asuquo et al 2013), in Figure 4b and the characteristic features of PN confirmed the diagnosis.…”
Section: Discussionmentioning
confidence: 84%
“…Reports have indicated that 25%~45% of extracranial schwannomas develop on the head and neck 3 . However, schwannoma development on the scalp is rare 4 5 6 . According to a study analyzing 22 patients with extracranial non-vestibular head and neck schwannomas, 76% were unilateral neck masses 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are very few cases of cutaneous schwannomas reported. As previously stated, they can occur anywhere on the body, including the scalp [3] , [4] , trunk [5] , and feet [6] . By reporting this case, we hope to further expand the literature on this pathology.…”
Section: Discussionmentioning
confidence: 99%